An Experimental Study of the Lingual Consciousness of Ukrainians and Russians (Dynamic Aspect) - Terekhova, Diana (East European Journal of Psycholinguistics, 2018)
The study of the lingual consciousness of various ethnic group representatives does not lose its topicality in psycholinguistic investigation for decades. During the period of the formation and development of psycholinguistics, scholars have gained considerable experience in holding associative experiments, the results of which are reflected in associative dictionaries and individual scientific investigations. This material is valuable in several aspects of the investigation in particular as an object of the study of the lingual consciousness of the certain language speakers for the duration of the experiment; in the comparable aspect for the identification of common and distinguishing features in the lingual consciousness of the representatives of different ethnic groups as well as to find out the changes in the lingual consciousness of a certain ethnic group members according to the experimental data received at a certain time interval etc. The article focuses on revealing the dynamics in the lingual consciousness of the representatives of the two East Slavic peoples. The experimental data were drawn both from lexicographic psycholinguistic works and from author’s experimental studies held in 2000 and 2012 representing the changes in the corresponding fragments of the world image in Ukrainians and Russians. References Жайворонок В. В. Знаки української етнокультури: Словник-довідник / В. В. Жайворонок. К.: Довіра, 2006. Марковина И. Ю., Данилова Е. В. Специфика языкового сознания русских и американцев: опыт построения «ассоциативного гештальта» текстов оригинала и перевода // Языковое сознание и образ мира / Отв. ред. Н. В. Уфимцева. М.: Институт языкознания РАН, 2000. С. 116-132. Степанов Ю. С. Константы: Словарь русской культуры: Изд. 2-е, испр. и доп. М.: Академический Проект, 2001. References (translated and transliterated) Zhaivoronok, V. V. (2006) Znaky Ukrayinckoyi Etnokultury: Slovnyk-Dovidnyk [Signs of the Ukrainian Ethnoculture: Dictionary-Reference Book]. Kyiv: Dovira. Markovina, I. U., Danilova, E. V. (2000) Spetsifika jazykovogo soznaniya russkih i amerikantsev: opit postrojenija “assotsiativnogo geshtalta” tekstov originala i perevoda [The peculiarity of the lingual consciousness of Russians and Americans: the experience of constructing an “associative gestalt” of the original and translation texts]. In: Yazykovoye Soznaniye i Obraz Mira, (pp. 116-132) .N. Ufimtseva, Ed. Moscow: Institute of Linguistics of the Russian Academy of Sciences. Stepanov, Yu. S. (2001). Konstanty: Slovar Russkoy Kultury: 2nd edition [Constants: Dictionary of the Russian Culture]. Moscow: Akademicheskiy Proekt. Джерела Бутенко Н. П. Словник асоціативних норм української мови. Львів: Вища школа, 1979. Ожегов С., Шведова Н. Толковый словарь русского языка. Режим доступа: https://classes.ru/all-russian/russian-dictionary-Ozhegov-term-10012.htm САС – Славянский ассоциативный словарь: русский, белорусский, болгарский, украинский / Н. В. Уфимцева, Г. А. Черкасова, Ю. Н. Караулов, Е.Ф. Тарасов. М., 2004. САНРЯ – Словарь ассоциативных норм русского языка / Под ред. А. А. Леонтьева. М.: Изд-во Моск. ун-та, 1977. Словник української мови: Академічний тлумачний словник (1970-1980). Т. 3. С. 557. Sources Butenko, N. P. (1979). Slovnyk Asotsiatyvnykh Norm Ukrayinckoyi Movy [Dictionary of the Associative Norms of the Ukrainian language]. Lviv: Vyshcha Shkola. Dictionary of the Ukrainian Language. (1970-1980). Vol. 3, P. 557. Ozhegov, S., Shvedova, N. The Explanatory Dictionary of the Russian Language. Retrieved from: https://classes.ru/all-russian/russian-dictionary-Ozhegov-term-10012.htm Slavyanskiy Assotsiativnyi Slovar: Russkiy, Belorusskiy, Bolgarskiy, Ukrainskiy (2004) [Slavic Associative Dictionary: Russian, Belorusian, Bulgarian, Ukrainian]. N. Ufimtseva, G. Cherkasova, Yu. Karaulov, Ye. Tarasov, (Eds). Moscow. Slovar Assocziativnyh Norm Russkogo Yazyka (1977). [Dictionary of Associative Norms of the Russian Language]. A. A. Leontyev, Ed. Moscow: Moscow University.